Refugees, Foreign Nationals, and Wageni: Comparing African Responses to Somali Migration. (March 2020) - Whitaker, Beth Elise
Abstract: Host governments have responded to the migration of Somali refugees throughout Africa in recent decades in different ways. Kenyan policymakers have treated Somalis primarily as a security threat, imposing restrictions on them that especially target this group. In South Africa, where economic and political competition fuel xenophobia, Somalis are part of a larger foreign national population that is seen as having disproportionate economic influence. However, Somali Bantus have been welcomed in Tanzania, which granted them citizenship even as it limited the mobility and activities of other refugees. A comparative analysis suggests that the relative balance among security, economic, political, and normative considerations shapes the extent and scope of host government policies. Résumé: les gouvernements hôtes ont réagi de différentes manières à la migration des réfugiés somaliens à travers L'Afrique au cours des dernières décennies. Les dirigeants kényans ont traité les Somaliens principalement comme une menace à la sécurité, imposant des restrictions les visant tout particulièrement. En Afrique du Sud, où la concurrence économique et politique alimente la xénophobie, les Somaliens font partie d'une population nationale étrangère plus importante et considérée comme exerçant une influence économique disproportionnée. Cependant, les Bantous somaliens ont été accueillis en Tanzanie, ce qui leur a octroyé la citoyenneté, même si cela a limité la mobilité et les activités d'autres réfugiés. Une analyse comparative suggère que l'équilibre relatif entre les considérations de sécurité, économiques, politiques et normatives conditionne l'étendue et la portée des politiques du gouvernement hôte. Resumo: Nas últimas décadas, a atitude dos governos africanos em relação às migrações de refugiados somalis tem assumido expressões variadas. No Quénia, os decisores políticos encaram os somalis sobretudo como uma ameaça à segurança, impondo restrições que afetam especificamente este grupo. Na África do Sul, onde a concorrência económica e política alimenta a xenofobia, os somalis integram a população de origem estrangeira que é vista como detendo uma influência económica desproporcionada. Todavia, os bantu da Somália são bem-vindos na Tanzânia, que lhes concedeu cidadania, mesmo quando impôs restrições à mobilidade e às atividades de outros refugiados. Uma análise comparativa sugere que a dimensão e a abrangência das políticas dos governos de acolhimento são determinadas por um equilíbrio relativo entre a segurança e considerandos de natureza económica, política e jurídica.